Hubungan Status Gizi dan Usia Ibu Hamil dengan Kejadian Pre Eklamsia di Ponek RSUD Waluyojati Kabupatenm Probolinggo - Marfuatun; Ekasari, Tutik; Hanifah, Iis (AHM Center, 2026)
Preeclampsia is a pregnancy complication characterized by increased blood pressure, proteinuria, and edema after 20 weeks of gestation, which can cause morbidity and mortality in both mother and baby. Various risk factors can influence the incidence of preeclampsia, including maternal nutritional status and age. This study aims to determine the relationship between maternal nutritional status and age with the incidence of preeclampsia at CEmONC RSUD Waluyo Jati, Probolinggo Regency. This study used a cross-sectional design with secondary data from the medical records of pregnant women at CEmONC RSUD Waluyo Jati. Nutritional status and maternal age were classified into risk groups. The sampling technique used in this study was purposive sampling with a total of 59 pregnant women as respondents during January–February 2025. The results showed that 20 pregnant women (33.9%) had nutritional risk, 19 pregnant women (32.2%) had age-relaed risk, and 22 respondents (37.3%) experienced preeclampsia. Data analysis using the chi-square test showed a significant relationship with a p-value = 0.000 (p < 0.005). This indicated that maternal nutritional status and age had a significant relationship with the incidence of preeclampsia. Therefore, monitoring nutritional status and age before pregnancy is important as an effort to detect and prevent preeclampsia earl.